2009
DOI: 10.1534/genetics.108.099994
|View full text |Cite
|
Sign up to set email alerts
|

The Silkworm Z Chromosome Is Enriched in Testis-Specific Genes

Abstract: The role of sex chromosomes in sex determination has been well studied in diverse groups of organisms. However, the role of the genes on the sex chromosomes in conferring sexual dimorphism is still being experimentally evaluated. An unequal complement of sex chromosomes between two sexes makes them amenable to sex-specific evolutionary forces. Sex-linked genes preferentially expressed in one sex over the other offer a potential means of addressing the role of sex chromosomes in sexual dimorphism. We examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
77
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 55 publications
15
77
0
Order By: Relevance
“…These studies did not take into account the lack or incompleteness of dosage compensation in birds Itoh et al 2007) so a word of caution is needed regarding the patterns. However, genes that become up-regulated in adult ovary are under-represented on chicken Z (Mank and Ellegren 2009), and an over-representation of testis-specific genes on Z is seen in the female heterogametic silkworm (Arunkumar et al 2009), in agreement with the observations reported herein.…”
Section: Discussionsupporting
confidence: 91%
“…These studies did not take into account the lack or incompleteness of dosage compensation in birds Itoh et al 2007) so a word of caution is needed regarding the patterns. However, genes that become up-regulated in adult ovary are under-represented on chicken Z (Mank and Ellegren 2009), and an over-representation of testis-specific genes on Z is seen in the female heterogametic silkworm (Arunkumar et al 2009), in agreement with the observations reported herein.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the question of sexual antagonism has been extensively addressed in the perspective of how selection maintains genes with differential benefit to males and females in sex linkage, and how this process contributes to sex chromosome evolution. Among other examples, the recent acquisition of 'male beneficial' genes by the mammalian X (Zhang et al, 2010), the abundance of testis-specific genes on the silkworm Z (Arunkumar et al, 2009), the close linkage of sexually selected colour genes to sex-determination loci in cichlids (Lande et al, 2001) and the presence of loci coding for male courtship display traits, involved in behavioural isolation, in the stickleback neosex chromosome (Kitano et al, 2009), all support sexually antagonistic gene content as an important factor in the evolutionary history of both ancestral and more recently derived sex chromosome systems. In birds, chromosome 4a contains the SOX3 gene, considered as a possible ancestral precursor of the male determination gene SRY.…”
Section: Discussionmentioning
confidence: 99%
“…For unknown reasons, the Z chromosome carries an overproportionate number of genes solely expressed in the testis (Arunkumar et al 2009;Walters and Hardcastle 2011).…”
Section: Constituents Of the Z Chromosomementioning
confidence: 99%